Effect of Mo content on hydrogen evolution reaction activity of Mo2C/C electrocatalysts. (28th April 2020) - Nadar, Ashish; Banerjee, Atindra Mohan; Pai, Mrinal R.; Antony, Rajini P.; Patra, A.K.; Sastry, P.U.; Donthula, H.; Tewari, R.; Tripathi, A.K.
Abstract: Recent research suggests that molybdenum carbide (β-Mo2 C) has the potential to be a cheap and active substitute for Pt-based electrocatalyst for hydrogen evolution reaction. In this article molybdenum carbide (Mo2 C) electrocatalysts immobilized on carbon support were synthesized and evaluated for hydrogen evolution reaction (HER). The quantity of Mo in the samples was varied to understand the effect of Mo content in Mo2 C/C electrocatalyst on the structure, morphology, electrochemical properties and HER. The Mo weight percentages determined by ICP-OES technique in four Mo2 C/C samples prepared were found as ~9.3, 15.8, 20.4 and 28.0. SAXS studies revealed that the pore size of the carbon increased with an increase in Mo content, most probably to accommodate the Mo2 C motifs. X-ray photoelectron spectra showed that the amount of low valent Mo increased as we increased the Mo content up to 20 wt % but decreased in the 28 wt % sample. All the samples were active for electrochemical HER with the sample having ~20 wt % Mo showing the highest activity and exhibited a Tafel slope of 69 mVdec −1 . Among all samples the 20 wt% Mo sample exhibited the highest electrochemical surface area (ECSA) of ~2.92 mFcm −2 and minimum charge transfer resistance for the HER. Thus, it is concluded that 20 wt% Mo in Mo2 C/C electrocatalyst evolves with ideal pore size, highest ECSA, smooth charge transfer and thus exhibits the best electrochemical properties for HER. Graphical abstract: Image 1 Highlights: Dispersed Mo2 C on vulcan carbon (β-Mo2 C phase): an effective electrocatalyst for HER. Excess carbon required in starting material to prepare Mo2 C/C by carburization. 20 wt % Mo content is best electrocatalyst composition for HER. Electrochemical active surface area follows the order in Mo wt.% as: 20 > 15 > 28~9. EIS studies reveal fastest charge transfer kinetics in 20 wt % Mo sample.